Effects of soil working techniques and stock type on the regeneration performance of Celtis australis in Northwestern Himalaya - Bhardwaj, D. R. (2017)
Celtis australis, an important indigenous agroforestry tree species of northwestern Himalaya, was evaluated for survival response and quantitative performance in relation to various soil working techniques and planting methods on dry hill slopes. Different soil working and planting techniques significantly influenced survival, height, collar diameter, above-ground biomass, root biomass, tap and total root lengths. Planting in trenches, ditches and inward sloping contour terraces (gradonies) was observed to be superior to the conventional pit planting technique. Planting of bare-root seedlings outperformed that of direct seeded stocks, with winter-planted bare-root seedlings and stumps (root-shoot cuttings) performing equally well. Establishment costs per plant at one year were lower for bare-root seedlings than for direct seeded stock. Costs of establishing stumps (root- shoot cuttings) were lower than those of bare-root seedlings when raised in small ridge ditches. The cost efficiency (yield index + planting cost) of bare-root seedlings irrespective of soil working techniques was markedly higher than that of direct seeded stock, whereas bare-root seedlings and stumps performed equally well in respect of cost efficiency. The cost efficiency irrespective of soil working technique and planting stock was markedly higher after five years than after the first year.